Host genetics and geography influence microbiome composition in the sponge Ircinia campana. Issue 11 (3rd September 2019) - Griffiths, Sarah M.; Antwis, Rachael E.; Lenzi, Luca; Lucaci, Anita; Behringer, Donald C.; Butler, Mark J.; Preziosi, Richard F.
Abstract: Marine sponges are hosts to large, diverse communities of microorganisms. These microbiomes are distinct among sponge species and from seawater bacterial communities, indicating a key role of host identity in shaping its resident microbial community. However, the factors governing intraspecific microbiome variability are underexplored and may shed light on the evolutionary and ecological relationships between host and microbiome. Here, we examined the influence of genetic variation and geographic location on the composition of the Ircinia campana microbiome. We developed new microsatellite markers to genotype I. campana from two locations in the Florida Keys, USA, and characterized their microbiomes using V4 16S rRNA amplicon sequencing. We show that microbial community composition and diversity is influenced by host genotype, with more genetically similar sponges hosting more similar microbial communities. We also found that although I. campana was not genetically differentiated between sites, microbiome composition differed by location. Our results demonstrate that both host genetics and geography influence the composition of the sponge microbiome. Host genotypic influence on microbiome composition may be due to stable vertical transmission of the microbial community from parent to offspring, making microbiomes more similar by descent. Alternatively, sponge genotypic variation may reflect variation in functional traits that influence the acquisition of environmental microbes. This study reveals drivers of microbiome variation within and among locations, and shows the importance of intraspecific variability in mediating eco‐evolutionary dynamics of host‐associated microbiomes. Abstract : For the first time, the authors show that intraspecific genetic variation affects microbiome composition in a marine sponge ( Ircinia campana ), with positive correlations observed between genetic and microbiome similarity. This has significant implications for our understanding of the ecological and evolutionary relationships between host and microbiome in this important model system.